Synthetic Routes to Polyethersulphones - J.B. Rose (CHIMIA)
The polyethersulphones are a group of polycondensates composed of aryl or aryl alkyl residues joined together with ether and with sulphone bonds. Many polymers of this general structure have been prepared in the laboratory, but so far commercial manufacture has been restricted to materials based on only three different repeat units. There are two main routes to these polymers; polysulphonylation whereby intermediates containing aryl ether groups are linked together with sulphone bonds in the polycondensation process and poly etherification when ether linkages are formed by polycondensation of aryl sulphone intermediates. These routes are complementary in that many structures made by one route can not be made by the other, but some structures can be made by either route. Choice of the route for building a particular repeat unit into polymer chains depends primarily on the availability of the appropriate intermediates, and advances in the synthesis of intermediates has increased the variety of structures that can be made, but the detailed chemistry of the polycondensation processes can lead to structural complications in the polymers and this limits the usefulness of certain intermediates.